Study of the effectiveness of teaching cultural geography in a school’s geography course - Satybaldieva, Ayzhan; Kaimuldinova, Kulyash; Laiskhanov, Shakhislam; Shakirova, Nurzhanat; Muzdybayeva, Karlygash (International Journal of Innovative Research and Scientific Studies, 2024)
The experience of countries with developed education and the work of scientists who have conducted research in this area indicate that cultural geography is the most important factor in the formation of the worldview of students. However, an analysis of the state of teaching cultural geography in secondary schools in Kazakhstan has shown that it is insufficiently studied. The cultural geography components of geography are included in school geography textbooks, although they are not specifically taught as an independent subject or course. Therefore, an elective course on Cultural Geography was developed to fill this gap, and its effectiveness was studied through experimental research. The general secondary education school in Almaty City was chosen as the base of the experiment. The experiment, in which a total of 50 students voluntarily participated, was conducted from September 2021 to the end of May 2022. In order to determine the educational levels of students after the course, three stages of monitoring were conducted and 15 tasks of different levels were given. The experiment’s findings demonstrated the significance of the elective "Cultural Geography" course in helping students develop their subject competencies and the value of implementing it in regular secondary schools.